Inventory strategy for spare parts redundancy to support server operations during production processes. Issue 1 (1st January 2019) - Lukitosari, Valeriana; Suparno; Pujawan, I. Nyoman; Widodo, Basuki
ABSTRACT: Inventory strategies are very necessary for supporting the production process. The strategy in the form of a model is proposed for redundant allocation of critical parts of a server system for minimizing additional costs. This model considers the occurrence of failure using downtime limits as the downtime on the server should be minimal. The rapid replacement of spare parts can be achieved through an onsite inventory or a redundant configuration. Furthermore, fast delivery would be an alternative when there is no inventory or redundancy. We considered four scenarios including a combination of stock, installation of redundant components, and fast deliveries. The model was solved using the Lagrangian relaxation method. No downtime in scenarios using redundancy resulted in a stable total cost over the last period, even though the penalty increased. The redundant module only had an additional cost in the initial period, so if the penalty value increased, there was a switching of scenario selection in the third or fourth scenario.